Maritime Dispute Resolution Between Kenya and Somalia from 2014-2021 Through the International Court of Justice - Britania Dyah Ayu Harefa; Mirsa Astuti (Eduvest - Journal of Universal Studies, 2025)
The maritime boundary dispute between Kenya and Somalia is one example of the rise of maritime disputes over natural resources. The dispute, which stems from different interpretations of boundaries in the Indian Ocean, has attracted the attention of the entire international community, especially on the African continent. In 2014, Somalia filed a lawsuit against Kenya in the International Court of Justice regarding the delimitation of maritime boundaries between the two coastal states. The International Court of Justice examined the basis of Somalia's lawsuit in proposing the settlement of the dispute. This study aims to determine the maritime zone boundary between Kenya and Somalia according to UNCLOS 1982, to determine the role of the International Court of Justice in resolving the dispute and to determine the legal impact of the International Court of Justice Decision regarding the maritime dispute between Kenya and Somalia. The research method used is normative law research with a statutory approach and a case approach. The results showed that the 1982 United Nations Convention on the Law of the Sea divided the maritime zone as inland waters, territorial sea, exclusive economic zone, and continental shelf. The International Court of Justice played an important role in determining the maritime boundary between Kenya and Somalia. The International Court of Justice's ruling has had a significant impact on the two countries' deteriorating bilateral relations, increasingly tense political relations, as well as impacting the security and socio-economic sectors in the East African region.